Death and Salvation in Ancient Egypt - Assmann, Jan (Book collections on Project MUSE., 2005)
"In his new book, Egyptologist Jan Assmann explores images of death and of death rites in ancient Egypt to provide new insights into the particular character of the civilization as a whole. Drawing on the unfamiliar genre of the death liturgy, he arrives at a comprehensive view of the religion of death in ancient Egypt." "Assmann describes in detail nine different images of death: death as the body being torn apart, as social isolation, the notion of the court of the dead, the dead body, the mummy, the soul and ancestral spirit of the dead, death as separation and transition, as homecoming, and as secret. Death and Salvation in Ancient Egypt also includes a discussion of rites that reflect beliefs about death through language and ritual."--Jacket